An integrated Qual/Quan strategy for ganglioside lipidomics using high‐resolution mass spectrometry and Skyline software. (2nd February 2021) - Ranasinghe, Asoka; Ciccimaro, Eugene; D'Arienzo, Celia; Olah, Timothy V.; Ponath, Paul; Hnatyshyn, Serhiy
Abstract : Rationale: Gangliosides (GS) are attractive targets in biomarker discovery because of their physiological significance in numerous human diseases including certain cancers and developmental and metabolic disorders. The robust strategy described here enables the profiling of numerous GS while obtaining quantitative data of exploratory biomarkers present in human plasma and whole blood. Method: The GS from human blood, human plasma, and several cell lines were extracted using a mixture of methanol and isopropanol/0.1% formic acid followed by direct analysis of the supernatant. The simultaneous Qualitative and Quantitative (Qual/Quan) approach involves micro flow (20 μL/min) high pressure liquid chromatography (HPLC)/high‐resolution mass spectrometry (HRMS) and post‐acquisition data processing with Skyline software for profiling numerous GS in biological matrices. The quantitative assay involves reverse‐phase liquid chromatography/HRMS and calibration curves using commercially available GS. Results: Protein precipitation resulted in ~60%–80% GS recovery from biological matrices. Direct injection of the extract allowed for quantification of targeted GS in human blood, plasma, and cancer cell lines. The lower limit of detection for the target analytes, GM1, GT1, GD1, spiked into 1% BSA/PBS, ranged from 1 to 10 ng/mL. Human lung cancer cell lines contained variable amounts (1–130 ng/mL) of soluble Fuc‐GM1 analogs, potential biomarkers of lung cancer. Conclusions: A combination of simple extraction and micro‐HPLC/HRMS allowed for quantification of GS in human serum and whole blood. Integration of HRMS with Skyline allowed for GS profiling in the same samples using post‐acquisition HRMS data without the need for reanalysis. The strategy presented here is expected to play an important role in profiling exploratory GS biomarkers in discovery bioanalytical research.